Students’ Perception toward English Online Assesment by Using Exambro - Syafryadin; Marzon Efendi (Journal of English for Specific Purposes in Indonesia, 2025)
The objective of the study is to find out the students’ perception toward English online assessment by using Exambro application. This research used descriptive quantitative methods. The data was collected by using a questionnaire from the eighth-grade students in one of favourite school. The questionnaire was adopted by the Shraim theory. It consists of six aspects, namely reliability, validity, pedagogy, security, practicality, and affective factors. This study involved 96 students who were separated into three classes. The SPSS program of computer was used in analysing the data from questionnaire. The data were analysed in quantitative way. The findings are the students have positive responses to all the aspects of perceptions toward online assessment. The highest mean is in security aspect. The mean is 4,13. Then the mean of validity (4,03), the reliability (3,80), the practicality (3,77), the pedagogy (3,50), the affective factors (3,30). From 18 statements in questionnaire, 17 statements got positive perception, while one perception which is about online assessment can reduce the stress and anxiety got the negative perception. The researcher suggests the next research to explore the parents’ perception toward online assessment by using Exambro application.